Crystal structures of the Cid1 poly (U) polymerase reveal the mechanism for UTP selectivity - Lunde, Bradley M.; Magler, Iris; Meinhart, Anton (Nucleic acids research, 2012)
Abstract. Polyuridylation is emerging as a ubiquitous post-translational modification with important roles in multiple aspects of RNA metabolism.